Autoimmune encephalitis associated with anti-SOX1 autoantibodies in COVID-19: A case report - Peter Sabaka; Gabriela Timárová; Mohammad Dababseh; Eliška Marešová; Igor Straka (IDCases)
Coronavirus disease 2019 (COVID-19) might be complicated by various non-respiratory conditions, including encephalitis. Encephalitis in COVID-19 represents a heterogenous group of diseases with variable aetiology. Autoimmune encephalitis (AIE) is the least common but one of the most severe causes of encephalopathy in COVID-19. AIE is a rare disease that is associated with different types of autoantibodies mostly directed against various neuronal antigens. Anti-Sry-like high mobility group box (SOX1) autoantibodies have been described in various clinical conditions, including Lambert-Eaton myasthenic syndrome, paraneoplastic cerebellar degeneration and rare cases of paraneoplastic AIE. We present the case of 28-year-old female patient with COVID-19 confirmed by the polymerase chain reaction (PCR) test. She was admitted with fever, headache, disorientation and new-onset refractory status epilepticus. Computed tomography and magnetic resonance imaging of the brain were unremarkable. Cerebrospinal fluid analysis showed pleocytosis, an increased total protein concentration and increased albumin and immunoglobulin G. Electroencephalography revealed findings suggestive of AIE. Serologic examination of antineuronal antibodies showed anti-SOX1 autoantibodies. A course of parenteral methylprednisolone and intravenous immunoglobulin led to rapid clinical improvement. The patient was discharged free of seizures as well as neurologic and psychiatric symptoms. After discharge, an oncologic screening was performed and ruled out a paraneoplastic aetiology.